Risking intensity : reading and writing poetry with high school students - Michaels, Judith, 1944- (Urbana, Ill. : National Council of Teachers of English, 1999)
Presents a personal approach to the teaching of poetry in high school classrooms, looking at the mind-body connection in the reading and writing of poems, and including examples of student and teacher writing, as well as the poems of published authors.
Includes bibliographical references (p. [165]-169).
Adult.
Adult
Keywords: Poetry -- Authorship; Poetry -- Study and teaching (Secondary); School verse, American; Children's writings; Poetics; Poetry -- Study and teaching